Demilitarization, the Military and the Post-Marcos Transition - Abinales, P.N. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Demilitarization is one of the biggest problems that the Aquino government must resolve as it was the same institution that supported the Marcos dictatorship. The February uprising saw the shifting of the military’s loyalty from Marcos to Aquino and from oppressors to heroes of democracy. Main issues confronting the Aquino government are the human rights violations. The military became deeply involved in the violation of human rights during the Marcos dictatorship and violence became a structural phenomenon and the military is perceived by the people as the main purveyor. The budget allocation as well will remain an issue as the threat of coups and the use of insurgency as a reason to maintain the current military budget. In order to demilitarize, the government should look at vital issues and such as broadening the meaning of national defense, ending military dependence on the United States, and institutionalizing civilian hegemony over the professional standing army. There is also the alternative of creating civilian army as an alternative.
Keywords: Post-Marcos; Aquino; demilitarization; human rights violations; US Bases; democratization of defense; civilian army; people’s army